Caring for children with disabilities in Kilifi, Kenya: what is the carer's experience? - Gona, J; Mung'ala-Odera, V; Newton, C; Hartley, S (2011)
BACKGROUND: Carers of children with disabilities have repeatedly highlighted their feelings of discrimination, stigma and exclusion in many domains of their lives. There is little research from Africa addressing these issues. This study investigated the challenges encountered by these carers and the mechanisms of coping with these challenges while caring for children with disabilities in a poor rural setting in Kenya. METHODS: Thirty-five in-depth interviews were conducted with 20 carers, 10 community members and 5 primary school teachers. Ten unstructured observations were also conducted in home environments to observe mechanisms used in meeting the needs of the children with disabilities. All interviews were tape-recorded, transcribed and translated from the local dialect. Note-taking was performed during all the observations. Data were stored in NVivo software for easy retrieval and management. RESULTS: The arrival of a disabled child severely impairs the expectations of carers. Hospital staff underestimate carers' emotional distress and need for information. Fear for the future, stress, rumour-mongering and poverty are encountered by carers. As they grapple with lost expectations, carers develop positive adaptations in the form of learning new skills, looking for external support and in some cases searching for cure for the problem. For their emotional stability, carers apply spiritual interventions and sharing of experiences. CONCLUSION: Despite the challenges faced by the carers, values and priorities in adaptation to the challenges caused by the child's disability were applied. It is recommended that these experiences are considered as they may influence programmes that address the needs of children with disabilities.